(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The aim of this research was to study the current state of the forests in Aleppo’s mountain and monitoring the change it has achieved, using NDVI during 2010-2016. The results of the study showed that the change in the forest cover of the pine (Pinus brutia Ten) and oak (Quercus calliprinos Webb) in Aleppo’s Mountain were significant in the years (2010, 2011, 2013, 2014, 2015 & 2016), and for all the years of study. The Normalized Vegetation Index (NDVI) showed generally low value of plants cover not exceeding 0.5.The highest NDVI values were in 2015 and the lowest value for both years 2010-2016 this is similar to Quercus calliprinos Webb. This study showed that this approach (NDVI) is a powerful and useful method of monitoring and forest cover managing.